Understanding the impact of fibroblast heterogeneity on skin fibrosis - Michelle F. Griffin; Heather E. desJardins-Park; Shamik Mascharak; Mimi R. Borrelli; Michael T. Longaker (The Company of Biologists, 2020)
Tissue fibrosis is the deposition of excessive extracellular matrix and can occur as part of the body's natural wound healing process upon injury, or as a consequence of diseases such as systemic sclerosis. Skin fibrosis contributes to significant morbidity due to the prevalence of injuries resulting from trauma and burn. Fibroblasts, the principal cells of the dermis, synthesize extracellular matrix to maintain the skin during homeostasis and also play a pivotal role in all stages of wound healing. Although it was previously believed that fibroblasts are homogeneous and mostly quiescent cells, it has become increasingly recognized that numerous fibroblast subtypes with unique functions and morphologies exist. This Review provides an overview of fibroblast heterogeneity in the mammalian dermis. We explain how fibroblast identity relates to their developmental origin, anatomical site and precise location within the skin tissue architecture in both human and mouse dermis. We discuss current evidence for the varied functionality of fibroblasts within the dermis and the relationships between fibroblast subtypes, and explain the current understanding of how fibroblast subpopulations may be controlled through transcriptional regulatory networks and paracrine communications. We consider how fibroblast heterogeneity can influence wound healing and fibrosis, and how insight into fibroblast heterogeneity could lead to novel therapeutic developments and targets for skin fibrosis. Finally, we contemplate how future studies should be shaped to implement knowledge of fibroblast heterogeneity into clinical practice in order to lessen the burden of skin fibrosis.